The Role of Vlog Project in Facilitating Authentic Speaking Assessment - Habibah, Nur; Pradana, Agsan Widy Kirana; Febrianty, Ervina; Musyarrofah, Hamdatul; Pradana, Muhammad Ilham Adhi (Edulitics (Education, Literature, and Linguistics) Journal, 2021)
To date, video blog (vlog) has been identified as a convenient learning tool to develop learners’ speaking skill. In language assessment, especially speaking, vlog has met the criteria for assessing learners’ speaking skill authentically since it provides real-life situations in the process of creating the video. This study aimed at investigating how vlog facilitates authentic assessment in measuring students’ speaking skill. This study is guided under a descriptive qualitative method using interview guidelines to collect the data and observation checklist in analysing the data. Two lecturers and six tertiary students from spoken English class were involved. The findings illustrate that the vlog project has acquired the criteria of authenticity of a speaking assessment as well as students’ preference in speaking assessment. The vlog project, therefore, can be advantageous media to assess students’ speaking skills authentically.